eCM 2003
DOI: 10.22203/ecm.v005a02
|View full text |Cite
|
Sign up to set email alerts
|

Haemocompatibility evaluation of DLC- and SiC-coated surfaces

Abstract: Diamond-like carbon (DLC) and silicon carbide (SiC) coatings are attractive because of low friction coefficient, high hardness, chemical inertness and smooth finish, which they provide to biomedical devices. Silicon wafers (Si waf ) and silicone rubber (Si rub ) plates were coated using plasmaenhanced chemical vapour deposition (PE-CVD) techniques. This article describes: 1-the characterization of modified surfaces using attenuated total reflection-Fourier transform infrared spectroscopy (ATR/FTIR) and contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 20 publications
1
50
0
Order By: Relevance
“…Three studies (on 2,125 patients) showed a benefit that was attributed to the SiC-coated stent (Elbaz et al, 2002;Hamm et al, 2003; Properties and Applications of Silicon Carbide 302 Kalnins et al, 2002). In a direct comparison of silicon wafers and SiC-coated (PECVD) silicon wafers for blood compatibility, both appeared to provoke clot formation to a greater extent than diamond-like coated silicon wafers; silicon was worse than SiC-coated silicon (Nurdin et al, 2003). In conclusion, the haemocompatibility of SiC was demonstrated.…”
Section: Haemocompatibilitymentioning
confidence: 84%
“…Three studies (on 2,125 patients) showed a benefit that was attributed to the SiC-coated stent (Elbaz et al, 2002;Hamm et al, 2003; Properties and Applications of Silicon Carbide 302 Kalnins et al, 2002). In a direct comparison of silicon wafers and SiC-coated (PECVD) silicon wafers for blood compatibility, both appeared to provoke clot formation to a greater extent than diamond-like coated silicon wafers; silicon was worse than SiC-coated silicon (Nurdin et al, 2003). In conclusion, the haemocompatibility of SiC was demonstrated.…”
Section: Haemocompatibilitymentioning
confidence: 84%
“…The protocol for scanning electron microscope (SEM) was modified from Nurdin and coauthors 19 and is described in the Appendix.…”
Section: Scanning Electron Microscope Imaging Of Sensor Surfacementioning
confidence: 99%
“…SiC is an attractive material for metal surface coatings, 1,2) photoelectrodes, 3) solar cells, 4) ultraviolet photodetectors, 5) power devices, 6,7) and other devices because it has excellent material properties such as a large energy band gap, a high chemical stability, a high robustness, a high thermal conductivity, and conductivity controllability through impurity doping. 8) These properties of SiC thin films are also preferable for the application of electrode coatings to water electrolysis technology.…”
Section: Introductionmentioning
confidence: 99%